Enhancing biomass conservation and enzymatic hydrolysis of sweet sorghum bagasse by combining pretreatment with ensiling and NaOH - Zhao, Shuai; Li, Hanyan; Sumpradit, Tawatchai; Khan, Aman (Frontiers in Microbiology, 2024)
Lignocellulosic pretreatment is an important stage in biomass utilization, which usually requires high input. In this study, a low-cost method using combined ensiling and NaOH was developed for lignocellulosic pretreatment. Sweet sorghum bagasse (SSB) was ensiled for 21 days and then treated with diluted NaOH (0%, 1%, and 2%) for fermentation. The results showed that the application of Lactobacillus plantarum (L) reduced fermentation losses of the silages, mainly low water-soluble carbohydrate (WSC) and ammonia nitrogen loss. Meanwhile, the application of Lactobacillus plantarum and ensiling enzyme (LE) promoted lignocellulosic degradation, as evidenced by low neutral detergent fiber (NDF), acid detergent fiber (ADF), lignin (ADL), and hemicellulosic (HC) contents. The dominant bacterial genera were Lactobacillus, uncultured_bacterium_f_Enterobacteriaceae, and Pantoea after silage, which corresponded to the higher lactic acid and acetic contents and lower pH. The reducing sugar yields of SSB increased after combined pretreatment of silage and NaOH and were further enhanced by the 2% NaOH application, as evidenced by the high reducing sugar yield and microstructure damage, especially in the L-2% NaOH group and the LE-2% NaOH group, in which the reducing sugar yields were 87.99 and 94.45%, respectively, compared with those of the no additive control (CK)-0 NaOH group. Therefore, this study provides an effective method for SSB pretreatment to enhance biomass conservation.